Favourable cost-benefit in an early defibrillation program using dual dispatch of ambulance and fire services in out-of-hospital cardiac arrest - Björn Sund; Leif Svensson; Mårten Rosenqvist; Jacob Hollenberg (Örebro University School of Business, 2010)
Aims: Out-of-hospital cardiac arrest (OHCA) is fatal without treatment and time to defibrillation is an extremely important factor in relation to survival. We performed a cost-benefit analysis of dual dispatch defibrillation by ambulance and fire services in the County of Stockholm, Sweden.Methods and Results: A cost-benefit analysis was performed to evaluate the effects of dual dispatch defibrillation. The increased survival rates were estimated from a real world implemented intervention and the monetary value of a life ( exteuro 2.2 million) was applied to this benefit by using results from a recent stated-preference study. The estimated costs include defibrillators (including expendables/maintenance), training, hospitalisation/health care, call-outs for the fire services, overhead resources and costs for the dispatch centre. The estimated number of additional saved lives was 16 per year, yielding a benefit-cost ratio of 36. The cost per quality-adjusted life years (QALY) was estimated to be exteuro 13 000 and the cost per saved life was exteuro 60 000. Conclusions: The intervention of dual dispatch defibrillation by ambulance and fire services in the County of Stockholm had positive economic effects. For the cost-benefit analysis the return on investment was high and the cost-effectiveness showed levels below the threshold value for economic efficiency used in Sweden. The cost-utility analysis categorises the cost per QALY as medium.
Keywords: D61; H43; I18; 330; Cost-benefit analysis; cost-utility analysis; cost-effectiveness analysis; cardiac arrest; defibrillation; ambulance; fire services